Relevansi dan Implementasi Pemikiran Nurcholish Madjid terhadap Politik Indonesia - M Munawar (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2019)
This paper is based on a literature study that aims to examine the relevance and implementation of Islamic politics in the political arena of Indonesia, the majority of which are Muslims. The results of the study concluded that in the era of 70s emerged ??Nurcholish Madjid's idea that "Islam YES, Islamic party NO" and it had established a new awareness for Muslims on the desired goal which is not idealism about the establishment of an Islamic State, but a just and prosperous society. Islam is no longer seen as a symbolic structure, but rather the spirit of values ??that are brought and developed in the life of the state. Efforts to articulate Islamic politics in Indonesia are important issues that need to be addressed to provide a possible synthesis between Islam and the State, therefore the study of Islamic political thought that is unique to Indonesia is not only attractive but urgent to do. In line with the conclusions above, it is expected that this paper can trigger students, especially those who choose the Department of Siyasah Jinayah so that Islamic political thought not only be a mere discourse but should be more focused on the aspect of its implementation to move towards a more advanced Indonesia.